ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN PADA PT.PEGADAIAN (PERSERO) CABANG MEGAMAS - Datulangie, Ricky Michael; Poputra, Agus Toni (ACCOUNTABILITY, 2016)
Companies are required to arrange their financial statements because it is the important basis to determine the recognition of revenues and expenses in accordance with the applicable rules. The research object in this case is PT. Pegadaian (Persero) Megamas Branch. The purpose was to determine and evaluate the implementation of the recognition of revenues and expenses in PT. Pegadaian (Persero) Megamas Branch. Data analysis is using qualitative method. The type of data is using primary data. Source of the data is using documentation method. This study found that the company adopted PSAK No. 23 (Revised 2010), Revenues, which identifies the fulfillment of the criteria of revenue recognition, the recognition of revenues and expenses done by using the accrual basis, and measurement of revenue recorded by the cash receipts in accordance with PSAK No. 23, paragraph 8.